Effect of outdoor air pollution on asthma exacerbations in children and adults: Systematic review and multilevel meta-analysis. - Pablo Orellano; Nancy Quaranta; Julieta Reynoso; Brenda Balbi; Julia Vasquez (PLoS ONE)
Background Several observational studies have suggested that outdoor air pollution may induce or aggravate asthma. However, epidemiological results are inconclusive due to the presence of numerous moderators which influence this association. The goal of this study was to assess the relationship between outdoor air pollutants and moderate or severe asthma exacerbations in children and adults through a systematic review and multilevel meta-analysis. Material and methods We searched studies published in English on PubMed, Scopus, and Google Scholar between January 2000 and October 2016. Studies following a case-crossover design with records of emergency departments and/or hospital admissions as a surrogate of moderate or severe asthma exacerbations were selected. A multilevel meta-analysis was employed, taking into account the potential clustering effects within studies examining more than one lag. Odds ratios (ORs) and 95% confidence intervals were estimated. A subgroup analysis in children aged 0 to 18 years and a sensitivity analysis based on the quality of the included studies as defined in the Newcastle-Ottawa Scale were performed. Publication bias was evaluated through visual inspection of funnel plots and by a complementary search of grey literature. (Prospero Registration number CRD42015032323). Results Database searches retrieved 208 records, and finally 22 studies were selected for quantitative analysis. All pollutants except SO2 and PM10 showed a significant association with asthma exacerbations (NO2: 1.024; 95% CI: 1.005,1.043, SO2: 1.039; 95% CI: 0.988,1.094), PM10: 1.024; 95% CI: 0.995,1.053, PM2.5: 1.028; 95% CI: 1.009,1.047, CO: 1.045; 95% CI: 1.005,1.086, O3: 1.032; 95% CI: 1.005,1.060. In children, the association was significant for NO2, SO2 and PM2.5. Conclusion This meta-analysis provides evidence of the association between selected air pollutants and asthma exacerbations for different lags.